PIC microcontroller based temperature measuring system using thermocouple sensor / Ahmad Yasir Md Zain - Md Zain, Ahmad Yasir (2008)
This project aims to design a temperature measuring device that can detect and read temperature by the user. This solution allows detecting and measuring high temperature environment by a thermocouple sensor. The output of sensor unit is connected to a Chip MAX6675. It is basically takes milivolts produced by the standard J-type thermocouple then amplifies and filter the unwanted signal and then converted it into digital and output the temperature reading by interfacing the MAX6675 and LCD with PIC microcontroller. The MPLab software component includes the programming code via the PIC microcontroller. A simple, rugged digital temperature meter (LCD 16x2 displays) will display the temperature detected. This report also presents my temperature project reading comparing with actual temperature taken from digital thermometer as a result. From the result show this device have high accuracy and small error but less precision.